1983
DOI: 10.1159/000233314
|View full text |Cite
|
Sign up to set email alerts
|

HLA-Related Lymphocyte Responsiveness in Psoriasis

Abstract: In order to find associations among the genetic, immunological and environmental factors that might be important in the pathogenesis of psoriasis, the relationship between streptococcal antigen- or mitogen-induced lymphocyte responses in vitro and HLA phenotypes was studied in 23 patients with psoriasis. Patients showed an elevated lymphocyte response to somatic A-streptococcal antigens when compared with healthy controls. In contrast, the response to mitogens (PHA, Con A, PWM) was impaired in patients with ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In psoriasis, so far, only circumstantial evidence links streptococcal infections to HLA-Cw*0602 status, mainly in the guttate phenotype [ 4 - 8 ]. HLA genotypes are reported to influence T-cell proliferation in response to streptococcal antigens in vitro [ 9 , 10 ] and streptococci are known to modulate immune responses through molecular mimicry [ 11 ]. In vitro studies show homology between streptococcal M-proteins and human keratins, which may influence T-cell responses [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In psoriasis, so far, only circumstantial evidence links streptococcal infections to HLA-Cw*0602 status, mainly in the guttate phenotype [ 4 - 8 ]. HLA genotypes are reported to influence T-cell proliferation in response to streptococcal antigens in vitro [ 9 , 10 ] and streptococci are known to modulate immune responses through molecular mimicry [ 11 ]. In vitro studies show homology between streptococcal M-proteins and human keratins, which may influence T-cell responses [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whether these associations are circumstantial or do indeed contribute to pathophysiology remains to be established. In the late 1970s, Gross et al (1977Gross et al ( , 1983 reported that, in psoriasis, T-cell functions in response to in vitro exposure to streptococcal factors are influenced by HLA-C genotypes. No additional reports addressing this phenomenon are available since then.…”
Section: Introductionmentioning
confidence: 99%